AlGaAs/GaAs heterojunction phototransistor with Zn delta-doped base region - Ściana, Beata; Radziewicz, Damian; Pucicki, Damian; Tłaczała, Marek; Kováč, Jaroslav; Srnanek, Rudolf (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
The paper presents the technology and characterisation of n-p-n AlGaAs/GaAs heterojunction phototransistor (HPT) with a thin (50 nm) Zn delta-doped GaAs base region. Such a construction of the HPT transistor was applied to obtain higher current gain and lower power consumption. The electrical and optical properties of the HPT transistor were examined using electrochemical capacitance-voltage (EC-V) measurements, photovoltage, photocurrent and micro-Raman spectroscopies. The measured and simulated I-U characteristics as well as results of time response measurements are also presented and discussed. All investigations were carried out without a base bias (“floating base”).
Optica Applicata, Vol. 35, 2005, nr 3, s. 645-650
Keywords: optyka; heterojunction phototransistor; Zn delta-doped GaAs; EC-V measurements; photovoltage spectroscopy; micro-Raman spectroscopy